2021
DOI: 10.3389/fnagi.2021.713819
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Deficiency Induces Mitochondrial Damage Prior to Emergence of Cognitive Deficits in a Postmenopausal Mouse Model

Abstract: Background: Estrogen deficiency contributes to the development of Alzheimer’s disease (AD) in menopausal women. In the current study, we examined the impact of estrogen deficiency on mitochondrial function and cognition using a postmenopausal mouse model.Methods: Bilateral ovariectomy was conducted in adult females C57BL/6J. Cognitive function was examined using the Morris water maze (MWM) test at 2 weeks, 1, 2, and 3 months after ovariectomy. Neurodegeneration was assessed using an immunofluorescence assay of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 97 publications
0
17
0
Order By: Relevance
“…The loss of antioxidant homeostasis negatively affects the quality of mitochondria in many tissues, including the brain [ 125 ], and antioxidant production seems to depend on E2 levels. Recently, Zhao et al [ 126 ] showed mitochondrial dysfunction and cognitive decline in a mouse model of ovariectomy-induced E2 deprivation.…”
Section: Estrogen and Metabolic Activitymentioning
confidence: 99%
“…The loss of antioxidant homeostasis negatively affects the quality of mitochondria in many tissues, including the brain [ 125 ], and antioxidant production seems to depend on E2 levels. Recently, Zhao et al [ 126 ] showed mitochondrial dysfunction and cognitive decline in a mouse model of ovariectomy-induced E2 deprivation.…”
Section: Estrogen and Metabolic Activitymentioning
confidence: 99%
“…In female AD patients, mtERβ expression and mitochondrial cytochrome C oxidase activity were significantly reduced, which implies that the deficiency of mtERβ might be associated with the dysfunction of mitochondria in AD [161]. A recent study showed that mitochondrial damage, including abnormal mitochondrial function and biogenesis, occurs prior to cognitive decline in the hippocampus of ovariectomized mice [162]. Compared to a premenopausal control, post-and perimenopausal females displayed reduced platelet mitochondrial activity, which was highly correlated to cerebral glucose metabolism [163].…”
Section: The Role Of Estrogen In Admentioning
confidence: 99%
“…Interestingly, insulin-induced hypoglycemia significantly decreases GPER protein expression in A2 noradrenergic nerve cells in females but not males [227], which indicates a sex difference in GPER gene expression regulation. In addition, ERα and ERβ are also expressed in mitochondria and against mitochondrial-mediated oxidative stress via a non-genomic pathway [228], and estrogen deficiency causes mitochondrial dysfunction prior to cognitive decline in ovariectomized mice [162].…”
Section: Non-genomic Pathway Signals Of Estrogenmentioning
confidence: 99%
“…Mitochondria are one of the essential cellular organelles for the induction of E2 effects [47]. Regulation of mitochondrial metabolism [24,48], cell death [49,50] and quality control [51,52] are a few examples by which E2 regulates cellular homeostasis. In this article, we discuss the mechanisms of E2 actions and its effects on mitochondrial function.…”
Section: Introductionmentioning
confidence: 99%